Business Process Orchestration BPEL supports time-critical decision making. - Zager, Matthew
Our journey began with our Department of Defense research projects when we saw an opportunity to solve our data management challenges with XML. The journey continued with the evolution of that work as it applied to exposing legacy data sources as XML through data-oriented Web services. We continue to build upon this foundation by broadening our service-oriented architecture (SOA) with these XML-enabled yet disjoint systems as we look to Business Process Execution Language (BPEL) to orchestrate their complex interactions.